PERAN ORANG TUA DAN GURU DALAM PENGARAHAN PENDIDIKAN ISLAM - Mudhoffar, Mudhoffar (LPPI Universitas Al-Qolam Malang, 2015)
Islamic education requires more attention today, especially in the era of globalization. Anyone who is not ready to compete, think and move fast, will be alienated or even crushed by the fast and dynamic wheels of globalization. Religious education is the process of transinternalization of knowledge and Islamic values to the learners through the undertakings of teaching, habituation, guidance, care, supervision, and development of their potential, in order to achieve perfection and harmony of life in this world and in the hereafter, both physically and spiritually. The role of parents and teachers in directing religious education is very important. They influence the process and the outcomes of education. However, it takes ways that parents can unify thoughts and perceptions with the teacher either through parenting or continuous communication, so that parents are aware of the need for moral and religious education of their children. Thus, the formation of morality and religion of the children can go through in balance; either children are in the home environment with his parents, or are in the school environment. Keywords: Islamic education, parents, teacher, balance.